15 years journey of idiopathic pulmonary arterial hypertension with BMPR2 mutation - Kyung Jin Ahn; Albert Youngwoo Jang; Su Jung Park; Wook-Jin Chung (BMC, 2019)
Abstract Pulmonary arterial hypertension (PAH) is known as one of diseases with the worst prognosis. Recently, targeted PAH drugs have been developed and approved for use; therefore, the treatment strategy and goals have changed, and the prognosis has improved over two decades. We reviewed the case of a female who showed the natural disease course of heritable PAH in treatment with the targeted PAH drugs under the Korean Health Insurance policy. At the age of 15, she visited the outpatient clinic for dyspnea on exertion that occurred 3 years ago. At that time, severe pulmonary hypertension was revealed by an echocardiography and there was no evidence of significant shunt lesion or embolism. After 4 years of loss to follow-up, her performance was WHO functional class III and she still suffered from dyspnea. The initial monotherapy using an endothelin receptor antagonist was started in 2008. After 2 years, BMPR 2 mutation was detected. Her clinical symptoms gradually worsened because of poor compliance. To escalate therapy, combination therapy was given, and finally, triple maximal therapy was maintained. The next step is to consider intravenous prostanoids. Various combinations of targeted therapy have been tried, and several trials have been confirmed that improve the prognosis. Initial upfront combination therapy and a more enthusiastic approach make good a better prognosis. In this area, active support of the government insurance policy is indispensable in Korea.